2014
DOI: 10.1002/etc.2781
|View full text |Cite
|
Sign up to set email alerts
|

Modeling PCB transfer into hen eggs: Influence of physiological characteristics of the animal

Abstract: Laying hens are likely to be exposed to a wide range of persistent organic pollutants (POPs), including polychlorinated biphenyls (PCBs). To improve the safety of poultry farming systems in terms of POPs, the present research focused on assessing the impact of physiological characteristics of the hen on the transfer of ingested PCBs to eggs. Modeling was used as a research tool to explore the impact of some physiological characteristics on the transfer of PCBs in the laying hen. The mathematical model simulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…At this point we clearly state that we assume that the ndl-PCB concentration is in equilibrium between muscle fat and other types of body fat. This assumption is supported by other studies and has been used before in modeling of chickens . The critical exploration of this assumption is an interesting subject for future studies.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…At this point we clearly state that we assume that the ndl-PCB concentration is in equilibrium between muscle fat and other types of body fat. This assumption is supported by other studies and has been used before in modeling of chickens . The critical exploration of this assumption is an interesting subject for future studies.…”
Section: Resultssupporting
confidence: 68%
“…This assumption is supported by other studies 16 and has been used before in modeling of chickens. 17 The critical exploration of this assumption is an interesting subject for future studies.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The time required to obtain uncontaminated milk that is in accordance with the regulation values depends on the speed of decontamination, that is, the half-life of the compounds in the organism. Indeed, the half-life is a function depending on the molecules’ characteristics and the physiological status of the animals, such as level of lactation, turnover of fat due to this lactation and fatness . Previous studies have shown that the PCB depuration kinetics in plasma follows a biphasic kinetic, , resulting in two successive half-lives.…”
Section: Discussionmentioning
confidence: 99%
“…This assumption is supported by other studies 14 and has been used before in modeling of chickens. 9,15 Due to the fact that the available datasets (Table 1) contain too few measurements of ndl-PCB concentrations in livers of laying hens, 13,16 the basis of the model for fattening chickens 9 is reduced to two compartments (Figure 1 and eqs 1−7): central compartment, which represents blood, and peripheral compartment, which represents total body fat excluding the brain. The values of physiological constants as well as a description of other model variables are presented in Table S1.…”
Section: ■ Materials and Methods (Including Safety Information)mentioning
confidence: 99%